Segmental dilatation of ileum in a child with juvenile idiopathic arthritis, localized myopathy with focal stasis induced immunogenic injury as a possible etiology: a case report - Santosh Kumar Mahalik; Susama Patra; Bikasha Bihary Tripathy; Akash Bihari Pati; Manoj Kumar Mohanty; Subash Chandra Samal (SpringerOpen, 2021)
Abstract Background Segmental dilatation of the intestine (SDI) though uncommon is a well-known entity and more than 150 cases of SDI are reported in the literature. The presentation and association of SDI are well described; however, the association of SDI with juvenile idiopathic arthritis (JIA) has not been reported earlier. We described a case of SDI with JIA, who presented with malnutrition and chronic abdominal distension. Case presentation A 5-year-old female child was getting treated for JIA and referred to us for evaluation of chronic abdominal distension. On laparotomy, a huge SDI was found approximately 40 cm from the ileocecal junction and resection of the dilated part with approximately 2-3 cm of healthy ileum on each side and anastomosis was performed. The child recovered well and the features of arthritis also resolute 6 weeks later. From histologic analysis, we have suggested role of localized myopathy in development of segmental dilatation. We have further emphasized the link between the SDI with development of arthritis. Conclusion Etiology of SDI is multifactorial with architectural malformation of the smooth muscle due to localized myopathy is the key. Focal stasis in SDI affecting permeability and increased exposure to macromolecules, and antigens may give rise to immune-mediated arthritis. Surgical management can reduce and cure the symptoms of such patients.